EVALUASI IMPLEMENTASI CPPB IRT DAN PENYUSUNAN REKOMENDASI HACCP PADA UMKM TEMPE XYZ DI BANDAR LAMPUNG - Wafi Adizara Muzakki; Okti Ruenda; Ilham Marvie; Novi Wijayanti; Ajeng Ayuningtias; Yuni Alfiyani Nurrahmah; Maysi Wulandari; Velinda Puspita Praja; Anggun Qoriyati (Jurusan Ilmu dan Teknologi Pangan Universitas Halu Oleo, 2025)
Tempe is a traditional Indonesian food produced through the fermentation of Rhizopus mold. During its production process, tempe is vulnerable to microbial contamination, which may lead to foodborne illnesses. Therefore, implementing a food safety system is essential to ensure product quality and increase consumer trust. This study aims to evaluate the compliance of Good Processed Food Production Methods for Home Industry (CPPB-IRT) and to develop a Hazard Analysis Critical Control Point (HACCP) plan at the Tempe XYZ MSME in Bandar Lampung. A descriptive quantitative approach was used, with primary data collected through direct observation and interviews, and secondary data from relevant documents and regulations. The evaluation results show that Tempe XYZ falls under IRTP level 4 due to 12 critical non-conformities, 15 serious, 3 major, and 1 minor non-conformity. Daily internal audits are recommended to support continuous improvement. The business has not yet implemented a HACCP system, but analysis identified five Critical Control Points (CCPs) at the stages of raw material reception, boiling, grinding, fermentation, and packaging. This study is expected to serve as a foundation for strengthening food safety management systems in small-scale tempe industries and supporting the quality improvement of traditional Indonesian food products.